Quality of life in children and adolescents with bipolar I depression treated with olanzapine/fluoxetine combination - Walker, Daniel J.; DelBello, Melissa P.; Landry, John; D’Souza, Deborah N.; Detke, Holland C. (Child and adolescent psychiatry and mental health, 2017)
We examined the efficacy of olanzapine/fluoxetine combination (OFC) in improving health-related quality of life (QoL) in the treatment of bipolar depression in children and adolescents. Patients aged 10-17 years with bipolar I disorder, depressed episode, baseline children's depression rating scale-revised (CDRS-R) total score ≥40, Young Mania Rating Scale (YMRS) total score ≤15, and YMRS-item 1 ≤ 2 were randomized to OFC (6/25-12/50 mg/day olanzapine/fluoxetine; n = 170) or placebo (n = 85) for up to 8 weeks of double-blind treatment. Patients and parents completed the revised KINDL questionnaire for measuring health-related QoL in children and adolescents (KINDL-R) at baseline and endpoint. The mean change in CDRS-R total and item scores were used to compare improvement in symptomatology in patients taking OFC and placebo. Tests were 2-sided using a Type I error cutoff of 0.05, and no adjustments for multiple comparisons were made. Baseline QoL as measured by the KINDL-R was substantially impaired relative to published norms for a healthy school-based sample. OFC-treated patients demonstrated an improvement over placebo at endpoint with respect to mean change from baseline in the patient-rated KINDL-R Self-esteem subscale score ( = 0.028), and in the parent KINDL-R ratings of emotional well-being ( = 0.020), Self-esteem ( = 0.030), and Family ( = 0.006). At endpoint, OFC-treated patients still had a lower QoL compared to the normative population. OFC showed significant improvement ( ≤ 0.05) versus placebo on the CDRS-R total score and on 7 of the 17 CDRS-R items. Patients aged 10-17 years with an acute episode of bipolar depression and their parents reported greater improvements (parents noticed improvements in more areas than did their offspring) on some aspects of QoL when treated with OFC compared with placebo. However, after 8 weeks of treatment, KINDL-R endpoint scores remained lower than those of the, presumably healthy, control population. A Study for Assessing Treatment of Patients Ages 10-17 with Bipolar Depression; http://www.clinicaltrials.gov; NCT00844857.